Evaluating the Influence of Drying Shrinkage on Cracking Resistance of Massive Self-Compacting Concrete with Blast Furnace Slag Using Finite Element Method - Benson Kipkemboi; Shingo Miyazawa (Infrastructures)
The application of self-compacting concrete in massive structures is still low due to the perceived high cracking tendency associated with high shrinkage and heat of cement hydration. This conclusion is from short-term research work of up to 3 months after casting. The purpose of this study is to evaluate the influence of drying shrinkage on the cracking resistance of massive self-compacting concrete with blast furnace slag using a three-dimensional finite element method of analysis (3D FEM). The restraint stress experiment results of the self-compacting concrete beam under drying conditions are compared with those of similar concrete beam models obtained from 3D FEM analysis. The value of the reduction coefficient for Young’s modulus of elasticity was proposed to consider the effect of stress relaxation due to creep in concrete. By using the proposed value of the reduction coefficient, thermal stress analysis was performed on a 1 m thick massive concrete wall member, and the cracking resistance of self-compacting concrete with different replacement ratios of blast furnace slag is discussed. By using the proposed reduction coefficient to evaluate concrete stress due to drying, the accuracy of thermal stress analysis results can be improved to a marginal error of ±15% from the experiment results. Also, the low-temperature rise caused by the high replacement ratio of blast furnace slag at 50% and 70%, respectively, contributed to improved cracking resistance. Furthermore, the optimum blast furnace slag replacement for better cracking resistance depends on the expected exposure condition of the structure.